MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS KONTEKSTUAL UNTUK MENINGKATKAN PEMAHAMAN KEAGAMAAN SISWA - Abdul Haris; Epi Nurlatip Budi (PT. IHLAS (Ilmu Adalah Segalanya) - BICARA CENTRE, 2026)
This study aims to analyze the effectiveness of a contextual-based Islamic Religious Education learning model in improving students’ religious understanding. Conventional learning often emphasizes memorization and theoretical mastery, making it difficult for students to connect religious values with daily life. Therefore, contextual learning is considered relevant because it links subject matter with students’ real-life experiences. This research employed a quantitative approach with a quasi-experimental design involving 60 students divided into experimental and control groups. Data were collected through tests, observations, and questionnaires. The findings showed that students taught using the contextual model experienced a significant improvement in religious understanding compared to those taught through conventional methods. The average post-test score of the experimental class reached 84.6, while the control class achieved 74.2. In addition, students in the experimental group demonstrated better attitudes in worship discipline, tolerance, honesty, and social responsibility. These results indicate that contextual learning can make Islamic Religious Education more meaningful, practical, and effective in strengthening students’ cognitive and affective competencies.